Analysis Of Students' Mistakes In Completing Exponent Materials Based On Castolan Theory - Mariani Mariani; Nahor Murani Hutapea; Maimunah Maimunah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This research is motivated by the importance of analyzing student errors in solving exponential problems, because there are still many students who make mistakes in solving exponential material problems. The purpose of this study was to find out the errors made by students in solving exponential problems using the Kastolan theory. The types of errors in the Kastolan theory are conceptual errors, procedural errors and technical errors. The type of research used is descriptive qualitative research. The subjects in this study were 31 students of class X8 SMAN 1 Kampar Timur. This study uses data collection techniques in the form of description tests and interviews. The description questions used in this study amounted to 5 questions related to the properties, equations and inequalities of the modified exponents. Data analysis is used in this study to reduce, present, and draw conclusions. Based on the results of the study, the percentage of students who made mistakes in working on exponential material problems were as follows: 1) Students made conceptual errors, with a percentage of 20.31%, 2) Students made procedural errors with a percentage of 35.55%, 3) Students made mistakes technique with a percentage of 44.12%. The mistakes that many students make on exponent material are procedural errors and technical errors.